Symposium 4: Addressing Methodological Issues In E-Learning Research: Symposium Introduction - Conole, Grainne (Proceedings of the International Conference on Networked Learning, 2004)
This symposium will consider methodological issues, which arise both from research using Information and Communication Technologies (ICT) and research into the use of ICT in learning and teaching. The symposium will begin with an overview of current research questions and a critique of methodological issues and common data collection and analytical techniques used in the area. It will then explore the relationship between theory and methods and research methodological issues in e-learning. Three case studies of specific examples, which explore these issues in more detail, are then presented.